Obszary zastosowań metod wyborów dyskretnych - Rybicka, Aneta (Area of Application of Discrete Choice Methods, 2006)
In preference measurement we use discrete choice methods, which represent the decompositional approach. These methods we use to: estimate market shares, consumer segmentation and define consumers' individual preference.The paper presents theoretical basis of discrete choice methods, their area of application and computer software used in preference research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 74-85